Ultra-Fast Degradation of p-Aminophenol by a Nanostructured Iron Catalyst - Rocio Benavente; David Lopez-Tejedor; Carlos Perez-Rizquez; Jose M. Palomo (Molecules, 2018)
Full degradation of p-aminophenol in aqueous solution at room temperature by using a heterogeneous nanostructured iron hybrid catalyst in the presence of hydrogen peroxide is described. A nanostructured iron catalyst was prepared by in situ formation of iron carbonate nanorods on the protein network using an aqueous solution of an enzyme, lipase B from Candida antarctica (CAL-B). A second kind of iron nanostructured catalyst was obtained by the sunsequent treatment of the hybrid with an aqueous liquid extract of Mentha x piperita. Remarkable differences were observed using TEM imaging. When M. piperita extract was used, nanoparticles appeared instead of nanorods. Catalytic activity of these iron nanocatalysts was studied in the degradation of the environmental pollutant p-aminophenol (pAP) under different operating parameters, such as pH, presence of buffer or hydrogen peroxide concentration. Optimal conditions were pH 4 in acetate buffer 10 mM containing 1% (v/v) H2O2 for FeCO3NRs@CALB, while for FeCO3NRs@CALB-Mentha, water containing 1% (v/v) H2O2, resulted the best. A complete degradation of 100 ppm of pAP was achieved in 2 and 3 min respectively using 1 g Fe/L. This novel nanocatalyst was recycled five times maintaining full catalytic performance.